Emotional anticipation of the school‐to‐work transition: A multigroup latent profile analysis. Issue 4 (31st October 2022) - Parmentier, Michaël; Pirsoul, Thomas; Bouchat, Pierre; Nils, Frédéric
Abstract: This study extends the investigation of future‐oriented emotions by investigating students' emotional anticipation profiles at the prospect of the school‐to‐work transition. Among 2882 students, latent profile analysis revealed the emergence of four qualitative and quantitative distinct profiles. We also examined the profile similarity across gender, educational type, and the remaining time before the transition. Men and women exhibited both qualitative (i.e., profile shape and prevalence) and quantitative (i.e., levels of profile indicators) differences. However, we found no quantitative differences with regard to the educational type and the remaining time before the transition. To the best of our knowledge, this research is the first to document the complex interaction between anticipatory and anticipated emotions and the suitability of a person‐centered approach for investigating emotional experience, especially among men and women. It provides essential practical information for developing a preventive strategy regarding the emotional anticipation of the school‐to‐work transition.